Gender Disparities in Otolaryngology: A Case Report Reflecting Global Perspectives. (26th October 2022) - Ali, Hawa M.; Lee, Stellina Y. H.; Jashek‐Ahmed, Farizeh; Seguya, Amina; Faucett, Erynne; Van Beck, Jenna; Stapleton, Emma; Peer, Shazia; Husain, Inna A.; Wiedermann, Joshua; Salano, Valerie; ,
Abstract : Objectives: To explore the impact of female sex on the experiences of trainees and surgeons in otolaryngology from LMIC and HIC. Methods: This study includes perspectives of five consultants and two resident physicians from the United States, United Kingdom, Uganda, Kenya and South Africa. Results: Six themes emerged from these interviews. Overall, LMIC and HIC women shared similar experiences of microaggressions during patients, working along ancillary staff, related to pregnancy, imposter syndrome, difficulties during job search, and unique barriers as consultant. Conclusions: The findings of this study highlight that gender disparities are present at all levels in Otolaryngology but can present differently depending on context. Laryngoscope, 133:547–551, 2023 Abstract :